MicroRNA-mediated regulation of BCL-2 in breast cancer - Kannan Mayuri; Sundaram Vickram; Thirunavukarasou Anand; Konda Mani Saravanan (AIMS Molecular Science)
Breast cancer, a prominent form of cancer in women, arises from the inner lining of mammary glands, ducts, and lobules. With an approximate prevalence rate of 1 in 8 women, the standard treatment methods for this condition include the surgical excision of afflicted tissues, chemotherapy, radiation, and hormone therapy. The BCL-2 gene, also known as the B cell lymphoma gene, prevents apoptosis in eukaryotic cells. It is commonly found to be excessively active in many types of malignancies, such as leukemia, carcinomas, and breast cancer. The excessive expression of this gene has a role in the advancement of cancer by inhibiting apoptosis. Recent research emphasizes the function of microRNAs (miRs) in regulating the expression of BCL-2. These miRs can either decrease or increase the activity of specific genes involved in programmed cell death, thus making them potential targets for therapeutic interventions. This review explicitly examines the regulatory impacts of several miRs on BCL-2, thereby investigating their ability to trigger apoptosis and function as targeted treatments for breast cancer. By comprehending the complex interplay between miRs and BCL-2, it is possible to devise novel therapeutic approaches that can augment the efficacy of breast cancer treatments, thus eventually enhancing patient outcomes.